Glucose-dependent effect of insulin receptor isoforms on tamoxifen antitumor activity in estrogen receptor-positive breast cancer cells - Stella, Stefania; Massimino, Michele; Manzella, Livia; Parrinello, Nunziatina Laura; Vitale, Silvia Rita; Martorana, Federica; Vigneri, Paolo (Frontiers in Endocrinology, 2023)
Breast cancer is the most common malignancy in women, and it is linked to several risk factors including genetic alterations, obesity, estrogen signaling, insulin levels and glucose metabolism deregulation. Insulin and Insulin-like growth factor signaling exerts a mitogenic and pro-survival effect. Indeed, epidemiological and pre-clinical studies have shown its involvement in the development, progression and therapy resistance of several cancer types including breast cancer. Insulin/Insulin-like growth factor signaling is triggered by two insulin receptors isoforms identified as IRA and IRB and by Insulin-like growth factor receptor I. Both class of receptors show high homology and can initiate the intracellular signaling cascade alone or by hybrids formation. While the role of Insulin-like growth factor receptor I in breast cancer progression and therapy resistance is well established, the effects of insulin receptors in this context are complex and not completely elucidated. Using estrogen-dependent with destroyed insulin-like growth factor receptor I gene (MCF7IGFIRKO) breast cancer cell models, selectively expressing IRA (MCF7IGFIRKO/IRA) or IRB (MCF7IGFIRKO/IRB), we investigated the role of insulin receptors on anti-proliferative activity of tamoxifen in presence of low and high glucose concentrations. We found that glucose levels played a crucial role in tamoxifen response mediated by IRA and IRB. High glucose increased the IC50 value of tamoxifen for both insulin receptors. IRA promoted cell cycle progression more than IRB, independently of glucose levels and insulin stimulation. IRB, in turn, showed anti-apoptotic properties, preserving cells survival after prolonged tamoxifen exposure, and negatively modulated pro-apoptotic genes when compared to IRA. Our findings suggest that glucose levels modify insulin receptors signaling and that this event can interfere with the tamoxifen therapeutic activity. The investigation of glucose metabolism and insulin receptor expression could have clinical implication in Estrogen Receptor positive breast cancer patients receiving endocrine treatments.